Desiccation of phyllosilicate-bearing samples as analog for desiccation cracks on Mars: Experimental setup and initial results. (June 2015) - El-Maarry, M.R.; Pommerol, A.; Thomas, N.
Abstract: The surface of Mars is host to many regions displaying polygonal crack patterns that have been identified as potential desiccation cracks. These regions are mostly within Noachian-aged terrains and are closely associated with phyllosilicate occurrences and smectites in particular. We have built a laboratory setup that allows us to carry out desiccation experiments on Mars-analog materials in an effort to constrain the physical and chemical properties of sediments that display polygonal cracks. The setup is complemented by a pre-existing simulation chamber that enables the investigation of the spectral and photometric properties of analog materials in Mars-like conditions. The initial experiments that have been carried out show that (1) crack patterns are visible in smectite-bearing materials in varying concentrations down to ~10% smectite by weight, (2) chlorides, and potentially other salts, delay the onset of cracking and may even block it from occurring entirely, and (3) the polygonal patterns, while being indicative of the presence of phyllosilicates, cannot be used to differentiate between various phyllosilicate-bearing deposits. However, their size-scale and morphology yields important information regarding their thickness and the hydrological conditions at the time of formation. Furthermore, the complementary spectral measurements for some of the analog samples shows that crack patterns may develop in materials with such low concentrations of smectites that would not be expected to be identified using remote-sensing instruments. This may explain the presence of polygonal patterns on Mars in sediments that lack spectral confirmation of phyllosilicates. Highlights: A platform for desiccation experiments is set up at the University of Berne. Samples with as little as 10% smectite content undergo cracking. Salts such as chlorides delay and may even prevent cracking. Crack patterns may constrain hydrological conditions but not mineralogy.